Analisis Determinan Penduduk Miskin di Provinsi Jawa Tengah Tahun 2015-2020 - Aditya Eka M.S Mahardika; Hendra Kusuma (Jurnal Ilmu Ekonomi, 2022)
This study aims to analyze the rate of economic growth, the human development index, the level of concern for the poor in Central Java Province in 2015 – 2020. The type of data used in this study is panel data. The tool used to perform the test is eviews9. The tests used in this study were FE, CE, RE, Chou, Hausman, LM, multiple linear regression and normality tests. The results show that the economic growth rate has a significant negative effect where the coefficient value is -0.043 with a probability value of 0.0475, the human development index has a significant negative effect where the coefficient value is -1.104 with a probability value of 0.0000, and the level of open partition has an insignificant effect with a coefficient 0.071 with a probability value of 0.2727.